First-order and higher-order inflation expectations: evidence about households and firms - Kieren, Pascal; König-Kersting, Christian; Schmidt, Robert J.; Trautmann, Stefan T.; Theurich, Franziska (Journal of economic behavior & organization, 2025)
We study the relationship between first-order and higher-order inflation expectations. Using two novel survey modules of German households and firms, we establish several new insights on the relation between different orders of beliefs. While our results are remarkably consistent for households and firm managers, they exhibit relevant differences to previous results documented in the literature. Most importantly, our results show that uncertainty aggregates when individuals think about the beliefs of others relative to their own beliefs. We derive implications for calibrating noisy information models with infinite regress and discuss potential sources for differences in results documented in the literature and their theoretical implications.